Boswellia sacra essential oil induces tumor cell-specific apoptosis and suppresses tumor aggressiveness in cultured human breast cancer cells - Suhail Mahmoud M; Wu Weijuan; Cao Amy; Mondalek Fadee G; Fung Kar-Ming; Shih Pin-Tsen; Fang Yu-Ting; Woolley Cole; Young Gary; Lin Hsueh-Kung (BMC, 2011)
Abstract Background Gum resins obtained from trees of the Burseraceae family (Boswellia sp.) are important ingredients in incense and perfumes. Extracts prepared from Boswellia sp. gum resins have been shown to possess anti-inflammatory and anti-neoplastic effects. Essential oil prepared by distillation of the gum resin traditionally used for aromatic therapy has also been shown to have tumor cell-specific anti-proliferative and pro-apoptotic activities. The objective of this study was to optimize conditions for preparing Boswellea sacra essential oil with the highest biological activity in inducing tumor cell-specific cytotoxicity and suppressing aggressive tumor phenotypes in human breast cancer cells. Methods Boswellia sacra essential oil was prepared from Omani Hougari grade resins through hydrodistillation at 78 or 100 oC for 12 hours. Chemical compositions were identified by gas chromatography-mass spectrometry; and total boswellic acids contents were quantified by high-performance liquid chromatography. Boswellia sacra essential oil-mediated cell viability and death were studied in established human breast cancer cell lines (T47D, MCF7, MDA-MB-231) and an immortalized normal human breast cell line (MCF10-2A). Apoptosis was assayed by genomic DNA fragmentation. Anti-invasive and anti-multicellular tumor properties were evaluated by cellular network and spheroid formation models, respectively. Western blot analysis was performed to study Boswellia sacra essential oil-regulated proteins involved in apoptosis, signaling pathways, and cell cycle regulation. Results More abundant high molecular weight compounds, including boswellic acids, were present in Boswellia sacra essential oil prepared at 100 oC hydrodistillation. All three human breast cancer cell lines were sensitive to essential oil treatment with reduced cell viability and elevated cell death, whereas the immortalized normal human breast cell line was more resistant to essential oil treatment. Boswellia sacra essential oil hydrodistilled at 100 oC was more potent than the essential oil prepared at 78 oC in inducing cancer cell death, preventing the cellular network formation (MDA-MB-231) cells on Matrigel, causing the breakdown of multicellular tumor spheroids (T47D cells), and regulating molecules involved in apoptosis, signal transduction, and cell cycle progression. Conclusions Similar to our previous observations in human bladder cancer cells, Boswellia sacra essential oil induces breast cancer cell-specific cytotoxicity. Suppression of cellular network formation and disruption of spheroid development of breast cancer cells by Boswellia sacra essential oil suggest that the essential oil may be effective for advanced breast cancer. Consistently, the essential oil represses signaling pathways and cell cycle regulators that have been proposed as therapeutic targets for breast cancer. Future pre-clinical and clinical studies are urgently needed to evaluate the safety and efficacy of Boswellia sacra essential oil as a therapeutic agent for treating breast cancer.